Unraveling how intermediary-beneficiary interaction shapes policy implementation - Cynthia L. Michel (Regulation & Governance, 2024)
As a result of policy growth, implementing agencies often face new mandates without the necessary capacity expansion to comply with, thus resorting to intermediaries. However, intermediaries are not innocuous to the implementation process, especially when they are expected to play the double role of target and intermediary, responsible for translating/interpreting regulation for beneficiaries. How does the interaction between beneficiaries and intermediaries-target shape policy implementation? I argue that such interaction is not only determined by the role the intermediary adopts, and their relation with the beneficiary, but also by the motivations beneficiaries have for engaging in the regulatory process, and their capacity to do so. I develop a theoretical framework for understanding their interaction and apply it to a new regulatory policy in Mexico to provide social security for paid domestic workers. I explore the mechanisms by which the interaction between intermediaries and beneficiaries affects the outcome of the regulatory process.
Keywords: 330; beneficiaries; labor regulation; paid domestic workers; policy growth; regulatory intermediaries